The effectiveness of a short course to improve coaches` knowledge on considerations for female athletes - Clarke, A.; Leabeater, A.; Suppiah, H.; Roberts, A. (Journal of Sports Sciences, 2024)
This study aimed to assess the effectiveness of an online short course in improving the knowledge and confidence of coaching and support staff when working with female athletes. A mixed-methods survey design was used, where participants completed surveys pre-, post-, and 6 months following an 8-week online course. Qualitative responses were analysed inductively using thematic analysis based on two pre-identified themes. Of the 92 participants who completed both pre- and post-course surveys, 72% (n = 66) were female and 67% (n = 62) were from team sports. Perceived knowledge and confidence improved following the course (p < 0.001) and were above pre-course values 6-months post (p < 0.001). A-priori theme Course Expectations generated two sub-themes: `Empowering [me] to empower and support [them]`, and "Sharing knowledge and experiences". A-priori theme Changes in Practice had subthemes of "Relaxing into it" and "Embedding support structures". Participants indicated that they enjoyed learning from a variety of content experts as well as other participants in an online format. Future courses aimed at coaching/support staff should design and deliver accessible programs aligned with the learning preferences of these individuals. When delivering specific education regarding supporting female athletes, targeting and encouraging men to participate may be beneficial.